2020
DOI: 10.1590/0102-311x00213920
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lockdown on the COVID-19 epidemic in Brazil: evidence from an interrupted time series design

Abstract: In response to the COVID-19 pandemic, governments worldwide have implemented social distancing policies with different levels of both enforcement and compliance. We conducted an interrupted time series analysis to estimate the impact of lockdowns on reducing the number of cases and deaths due to COVID-19 in Brazil. Official daily data was collected for four city capitals before and after their respective policies interventions based on a 14 days observation window. We estimated a segmented linear regression to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 19 publications
(19 reference statements)
1
40
0
9
Order By: Relevance
“…Embora Belém, Fortaleza e Recife tenham adotado lockdown em maio, semanas depois do pico epidêmico de abril (InfoGripe. https://gitlab.procc.fiocruz.br/mave/repo/-/tree/master/Boletins%20 do%20InfoGripe/Imagens/Capitais, acessado em 03/Nov/2020), a sua implantação parece ter tido impacto favorável sobre a diminuição do número de casos novos e de mortes devido à COVID-19 40 , o que pode ter limitado percentuais de mortes excedentes ainda maiores nas semanas seguintes.…”
Section: Resultsunclassified
“…Embora Belém, Fortaleza e Recife tenham adotado lockdown em maio, semanas depois do pico epidêmico de abril (InfoGripe. https://gitlab.procc.fiocruz.br/mave/repo/-/tree/master/Boletins%20 do%20InfoGripe/Imagens/Capitais, acessado em 03/Nov/2020), a sua implantação parece ter tido impacto favorável sobre a diminuição do número de casos novos e de mortes devido à COVID-19 40 , o que pode ter limitado percentuais de mortes excedentes ainda maiores nas semanas seguintes.…”
Section: Resultsunclassified
“…A limited number of ITS analyses have been conducted in this regard, and all of them showed that social distancing is effective in reducing the number of cases related to COVID-19 [ 16 , 17 ]. Silva et al found a statistically significant reduction in new confirmed cases in different state capitals in Brazil after a period of lockdown ranging from 13 to 23 days [ 16 ]. Tobías et al also reported a reduction in daily cases and ICU admission after the implementation of strict measures in Italy and Spain [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work it was also noticed that a higher percentage continues to just go out to work showing the economic need of the population. According to the literature [30][31][32][33] , attitudes that don't follow social isolation and that prioritize economics above all, as the political position of Brazil president of the current year -2020, contribute to a greater number of hospitalizations and deaths resulting from COVID-19.…”
Section: Discussionmentioning
confidence: 99%